World Religions in the World - David Chidester (Journal for the Study of Religion)
The classification of ‘world religions’ is highly problematic because of its arbitrary construction, its exclusion of indigenous religions, and its easy availability for ideological manipulation. The imperial edifice of ‘world religions’ has been dismantled in recent scholarship in the study of religion. Yet, the notion of ‘world religions’ has been enthusiastically embraced by advocates of inclusive citizenship in democratic societies and by advocates of indigenous empowerment in postcolonial societies. This brief essay reviews the terms of engagement for critically reflecting on the various deployments of ‘world religions’ as a prelude to thinking about religion in the world.